2015
DOI: 10.1037/a0037520
|View full text |Cite
|
Sign up to set email alerts
|

CBM reading, mathematics, and written expression at the secondary level: Examining latent composite relations among indices and unique predictions with a state achievement test.

Abstract: A paucity of research has examined the utility of curriculum-based measurement (CBM) for data-based decision making at the secondary level. As schools move to multitiered systems of service delivery, it is conceivable that multiple screening measures will be used that address various academic subject areas. The value of including different CBM indices measures is not well understood. The purpose of this study was to (a) examine the relationship among a variety of reading, writing, and mathematics CBM indices a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 62 publications
(142 reference statements)
3
26
0
Order By: Relevance
“…Although we found correlations between M‐CBM computation and NC‐EOG‐M that were statistically significant, the magnitude of the relationships were much weaker than those found in previous studies, including most studies that were conducted with secondary students (Foegen, ; Foegen & Deno, ; Helwig, Anderson, & Tindal, ; Helwig & Tindal, ). Only one recent study reported similar findings in regard to M‐CBM computation (Codding et al., ). Using structural equation modeling, researchers found that while computation M‐CBM probes were moderately correlated with math outcomes on a high‐stakes test, M‐CBM did not contribute significant unique prediction beyond the contribution of R‐CBM scores.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…Although we found correlations between M‐CBM computation and NC‐EOG‐M that were statistically significant, the magnitude of the relationships were much weaker than those found in previous studies, including most studies that were conducted with secondary students (Foegen, ; Foegen & Deno, ; Helwig, Anderson, & Tindal, ; Helwig & Tindal, ). Only one recent study reported similar findings in regard to M‐CBM computation (Codding et al., ). Using structural equation modeling, researchers found that while computation M‐CBM probes were moderately correlated with math outcomes on a high‐stakes test, M‐CBM did not contribute significant unique prediction beyond the contribution of R‐CBM scores.…”
Section: Discussionsupporting
confidence: 54%
“…Although these correlations were significant, MAZE alone only explained 9–11% of the variance in EOG scores. In contrast, previous studies that have examined the relationship between MAZE scores and math outcomes have found that reading comprehension as measured by MAZE was a significant predictor of math performance (Codding et al., ; Rutherford‐Becker & Vanderwood, ; Thurber et al., ).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations